(3QSGdI aj GdSja hGdbdes
(3ChdgG (B:s
(3bGd CMeO Hf eMeO Hf GdMLGRi ai cJGHg ChV GdCOH GdHGH GdQGHY ai GdfTQjGJ hajg aUdGf GdaUd GdChd ai GdeaGNQGJ s
(3BNQgG (B:s
(3hEfJUQ ef dGdg bhI hdG fGUQ hGeJY HXdGd ebGeg GdPi dGJcSQ GdCjGe ebOGQg agh LGHQ hdGJLHQg agh cGSQ Ef TGA Gddg JYGdi BNQ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
Keywords: (3GdeLGejYs